Book review (Old Testament essays, 1988)
In this book lecturers from Biblical Studies at Unisa discuss four themes relevant for their students as well as for modern readers. They claim that the four themes treated, namely creation, justice, faith and the Church link up with other. For the purpose of this review I will pay attention to the first two, which concern Old Testament studies.